Diagnostic performance of adenosine deaminase for abdominal tuberculosis: A systematic review and meta-analysis - Zhou, Ruixi; Qiu, Xia; Ying, Junjie; Yue, Yan; Ruan, Tiechao; Yu, Luting; Liu, Qian; Sun, Xuemei; Wang, Shaopu; Qu, Yi; Li, Xihong; Mu, Dezhi (Frontiers in Public Health, 2022)
Background and aim Abdominal tuberculosis (TB) is a common type of extrapulmonary TB with an insidious onset and non-specific symptoms. Adenosine deaminase (ADA) levels increase rapidly in the early stages of abdominal TB. However, it remains unclear whether ADA serves as a diagnostic marker for abdominal TB. Methods We performed a systematic literature search for relevant articles published in PubMed, Web of Science, Cochrane Library, and Embase up to April 2022. First, we used the Quality Assessment of Diagnostic Accuracy Studies tool-2 (QUADAS-2), to evaluate the quality of the included articles. Bivariate and hierarchical summary receiver operating characteristic (HSROC) models were then utilized to analyze pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR) and area under the receiver operating characteristic curve (AUROC). In addition, we explored a subgroup analysis for potential heterogeneity and publication bias among the included literature. Results Twenty-four articles (3,044 participants, 3,044 samples) which met the eligibility criteria were included in this study. The pooled sensitivity and specificity of ADA for abdominal TB detection were 93% [95% confidence interval (CI): 0.89–0.95] and 95% (95% CI: 0.93–0.96), respectively. PLR and NLR were 18.6 (95% CI: 14.0–24.6) and 0.08 (95% CI: 0.05–0.12), respectively. DOR and AUROC were 236 (95% CI: 134–415) and 0.98 (95% CI: 0.96–0.99), respectively. Furthermore, no heterogeneity or publication bias was found. Conclusions Our meta-analysis found ADA to be of excellent diagnostic value for abdominal TB and could be used as an auxiliary diagnostic tool. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42022297931.